2009
DOI: 10.1002/jor.20812
|View full text |Cite
|
Sign up to set email alerts
|

Collagen I membranes for tendon repair: Effect of collagen fiber orientation on cell behavior

Abstract: Tendons have poor spontaneous regenerative capabilities, and complete regeneration is never achieved despite intensive remodeling. In this in vitro study, we characterized two multilamellar collagen I membranes differing in the arrangement of collagen fiber deposition (oriented vs. nonoriented) and compared their mechanical properties. Human dermal fibroblasts and tenocytes were seeded on the two membranes to evaluate the effect of fiber orientation on cell viability and cytoskeletal organization. Results demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 25 publications
3
56
0
1
Order By: Relevance
“…These observations support the concept of a beneficial effect of these drug combination on the prevention of osteopenia in ovariectomised animals . Interestingly recent experimental studies have shown that the association of Vitamin K and D stimulates in vitro osteoblast differentiation in fracture site derived human mesenchymal stem cells (Gigante et al, 2008). These findings are suggestive of an additional target for reparative treatments.…”
Section: Combined Treatment With Vitamin K2 and Vitamin D3 In Ovariecmentioning
confidence: 90%
“…These observations support the concept of a beneficial effect of these drug combination on the prevention of osteopenia in ovariectomised animals . Interestingly recent experimental studies have shown that the association of Vitamin K and D stimulates in vitro osteoblast differentiation in fracture site derived human mesenchymal stem cells (Gigante et al, 2008). These findings are suggestive of an additional target for reparative treatments.…”
Section: Combined Treatment With Vitamin K2 and Vitamin D3 In Ovariecmentioning
confidence: 90%
“…sterilization, cell rinsing, freeze drying, etc. ); therefore these types of grafts are not viable in nature because their cellular structures are commonly destroyed during sterilization and other important tissue processing [72][73][74][75][76][77][78][79][80][81][82][83][84][85]. Therefore, it is a fact that the allo-and xenografts have significantly lower incorporative properties with the healing tissue and this is another major limitation which results in rapid absorption of the graft during tendon or ligament healing [69,72].…”
Section: Graft Options In Managing Large and Massive Tendon And Ligammentioning
confidence: 99%
“…This method of tissue engineering has been used for many years to decrease the antigenicity of the viable grafts [68][69][70][71][72]. Newer approaches have been developed by many and newer tissue engineered products are introduced in the recent years [73][74][75][76][77][78][79][80][81][82][83][84][85]. Basically, tissue engineering could be divided into four major categories including tissue scaffolds, healing promotive factors, stem cells and gene therapy [12].…”
Section: Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Tendons are slowly healed after injury with a poor spontaneous regeneration ability (Gigante et al, 2009;Song et al, 2010). Oryan et al (2010) classified tendon injuries into acute and chronic, and they demonstrated that it also could be categorized by etiology; the most significant tendon injuries involved sharp tendon ruptures, tendinopathic forms of tendon ruptures and congenital or acquired defects which are characterized by impaired healing response.…”
Section: Introductionmentioning
confidence: 99%